2009
DOI: 10.2337/db08-0473
|View full text |Cite
|
Sign up to set email alerts
|

Lipoic Acid Synthase (LASY)

Abstract: OBJECTIVE-Lipoic acid synthase (LASY) is the enzyme that is involved in the endogenous synthesis of lipoic acid, a potent mitochondrial antioxidant. The aim of this study was to study the role of LASY in type 2 diabetes.RESEARCH DESIGN AND METHODS-We studied expression of LASY in animal models of type 2 diabetes. We also looked at regulation of LASY in vitro under conditions that exist in diabetes. Additionally, we looked at effects of LASY knockdown on cellular antioxidant status, inflammation, mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 15 publications
2
57
0
2
Order By: Relevance
“…As a redox regulator, R-LA is a well known powerful mitochondrial antioxidant (37,38). In addition, we found that R-LA could activate HsmtKAS expression, suggesting that additional lipoic acid stimulated its own production, which is consistent with previous studies that exogenously administered lipoic acid increases lipoic acid synthase expression (39). Likewise, the effect of C75 treatment on HsmtKAS expression might due to decreased R-LA content.…”
Section: Discussionsupporting
confidence: 91%
“…As a redox regulator, R-LA is a well known powerful mitochondrial antioxidant (37,38). In addition, we found that R-LA could activate HsmtKAS expression, suggesting that additional lipoic acid stimulated its own production, which is consistent with previous studies that exogenously administered lipoic acid increases lipoic acid synthase expression (39). Likewise, the effect of C75 treatment on HsmtKAS expression might due to decreased R-LA content.…”
Section: Discussionsupporting
confidence: 91%
“…ALA can be also synthesized through enzymatic reactions in plants and animals' mitochondria from octanoic acid and cysteine (as a sulphur donor) (Padmalayam et al 2009;Szeląg et al 2012).…”
Section: Silymarinmentioning
confidence: 99%
“…A recent study has demonstrated that down-regulation of lipoic acid synthase (LASY), the enzyme involved in the endogenous synthesis of LA, reduced endogenous levels of LA as well as critical components of the antioxidant defence network, increasing oxidative stress. Moreover, this down-regulation of LASY induced a significant loss of mitochondrial membrane potential and decreased insulin-stimulated glucose uptake in skeletal muscle cells along with an increased inflammatory response which, in turn, leads to increased insulin resistance, mitochondrial dysfunction and inflammation [11]. Thus, LA can be considered as a promising therapeutic approach for chronic inflammatory diseases such as diabetes and obesity [12,13].…”
Section: Introductionmentioning
confidence: 99%